Implementasi Marketing Public Relations dalam Live Shopping Instagram Geggo Women - Kukuh Mudawisika; Nurrahmawati (Bandung Conference Series: Public Relations, 2022)
Abstract. Currently, the technological era has begun to develop rapidly, as well as a dynamic marketing public relations Implementation following its development. Various companies, especially in the clothing sector, are competing to market their products through various social media such as Instagram, Tiktok, and so on. Likewise with Geggo Women. Geggo Women is a hijab brand that stands under the auspices of PT. Latallah Jaya Abadi. Geggo Women has a unique selling method, which is called live shopping. Geggo Women maximizes the features provided on Instagram, because Instagram is the main medium in marketing their products. This live shopping uses the live feature. Geggo Women do this live shopping for 2 days, and every day Geggo Women live for 2 hours. On this occasion, the author made a research on "Marketing Public Relations Strategy in Live Shopping Instagram Geggo Women 12.12". This research uses a qualitative method, and a case study approach. The case study that the researcher examines is the Live Shopping Geggo Women phenomenon which was held on December 12, 2020 using Thomas L. Harris' Three ways strategy theory. This study uses data collection techniques with interviews, observations and literature. This research was conducted with the aim of; to find out the reason for Geggo Women using the live shopping method on Instagram, to find out the process of Geggo Women making the concept of live shopping on Instagram, to find out the process of Geggo Women carrying out live shopping on Instagram, to find out the obstacles faced by Geggo Women in implementing live shopping on Instagram. Abstrak. Saat ini, era teknologi sudah mulai berkembang pesat, begitupun dengan implementasi marketing public relations yang dinamis mengikuti perkembangannya. Berbagai perusahaan, kususnya dibidang pakaian berlomba-lomba memasarkan produknya melalui berbagai media sosial seperti Instagram, Tiktok, dan lain sebagainya. Begitupun dengan Geggo Women. Geggo Women adalah sebuah brand hijab yang berdiri dibawah naungan PT. Latallah Jaya Abadi. Geggo Women memiliki metode penjualan yang unik, yaitu yang bernama live shopping. Geggo Women memaksimalkan Fitur yang disediakan didalam Instagram, karena Instagram adalah media utamanya dalam memasarkan produknya. Live shopping ini menggunakan fitur live. Geggo Women melakukan live shopping ini selama 2 hari, dan disetiap harinya Geggo Women melakukan live selama 2 jam. Pada kesempatan kali ini, penulis membuat penelitian mengenai “Strategi Marketing Public Relations dalam Live Shopping Instagram Geggo Women 12.12”. Penelitian ini menggunakan metode Kualitatif, dan pendekatan studi kasus. Studi kasus yang peneliti kaji ialah fenomena Live Shopping Geggo Women yang digelar pada tanggal 12 Desember 2020 dengan menggunakan teori Three ways strategy Thomas L. Harris. Penelitian ini menggunakan teknik pengumpulan data dengan wawancara, observasi dan kepustakaan. Penelitian ini dilakukan dengan tujuan; untuk mengetahui alasan Geggo Women menggunakan metode live shopping pada Instagram, untuk mengetahui proses Geggo Women membuat konsep live shopping pada Instagram, untuk mengetahui proses Geggo Women melaksanaan live shopping pada Instagram, untuk mengetahui hambatan yang ditemui oleh Geggo Women dalam pelaksanaan live shopping pada Instagram.